(untitled) (International Journal of Nursing Education, 2020)
Background: Post-traumatic stress disorder, or PTSD, is the psychiatric disorder that can result from theexperience or witnessing of traumatic or life-threatening events such as terrorist attack, violent crime andabuse, military combat, natural disasters, serious accidents or violent personal assaults.Aims and Objectives: Aim of the study is,to assess the effectiveness of video assisted teaching programregarding PTSD among primary teachers in selected primary school.1. To assess the pre test knowledge regarding post traumatic stress disorder among the primary teachers.2. To evaluate the effectiveness of video assisted teaching program regarding post traumatic stress disorderamong primary teachers.3. To find out the association of post test knowledge score with their selected demographic variables.Material and Method: The study design was pre experimental research design, one group pretest posttest approach. primary teacher of Rashtrasant tukdoji primary school Wardha, lokvidhalay primary schoolWardha, savitribai primary school Wardha, zilla parishad primary school neri, zilla parishad primary schooldighi, zilla parishad primary school selsura, madhav dnyanpeeth hinganghat sample size were 30.Result: After the detailed analysis of the conducted study leads to the following conclusion that Meanknowledge score of the primary teacher in pre test was 7.33 ± 2.225 and in post test it was 24.43±1.499.Conclusion: The findings shows significant difference between pre test and post test that is After thecompletion of this study it is revealed that video assisted teaching program on knowledge regarding posttraumatic stress disorder among the primary teachers improving knowledge in that majority of primaryteacher had (26.66%) good and (20%) excellent level of knowledge score in post test. Statistically interpretedthat video assisted teaching programme is effective on knowledge regarding, post traumatic stress disorder(PTSD) among primary teachers. Thus H1 is accepted.